2009
DOI: 10.1021/jp909297d
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecular Glasses Based on Multiposition Encapsulated Phenyl Benzimidazole Iridium(III) Complexes: Toward Efficient Solution-Processable Host-Free Electrophosphorescent Diodes

Abstract: Three electrophosphorescent small molecular Ir(3+) complexes, Ir(HexPhBI)(3) 1 (HexPhBI = 1-Hexyl-2-phenyl-1H-benzo[d]imidazole), Ir(CzPhBI)(3) 2 (CzPhBI = 9-(6-(2-phenyl-1H-benzo[d]imidazol-1-yl)hexyl)-9H-carbazole), and Ir(Cz(2)PhBI)(3) 3 (Cz(2)PhBI = 9-(6-(4-(1-(6-(9H-carbazol-9-yl)hexyl)-1H-benzo[d]imidazol-2-yl)phenoxy)hexyl)-9H-carbazole), were synthesized in which 3 was designed with the structure of multiposition encapsulation. Compared to the hexyl-substituted 1, 2 and 3 end-capped with the conjugated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 46 publications
(69 reference statements)
0
17
0
Order By: Relevance
“…Successful example of enhancing the efficiency of Ir(III) complexes by introducing bulky side groups into ligands has also reported by Xu and his-cowokers [39,40]. However, there were few reports about improvement of quantum efficiency for cationic Ir(III) complexes by increasing the steric hindrance of complexes [41e46], especially through grafting the rigid ring end-capped aliphatic chains, such as carbazole-9-yln-butyl group (here, abbreviated as 'CZB'), on the biscyclometalated ligands and/or ancillary ligands of cationic Ir(III) complexes.…”
Section: Introductionmentioning
confidence: 77%
“…Successful example of enhancing the efficiency of Ir(III) complexes by introducing bulky side groups into ligands has also reported by Xu and his-cowokers [39,40]. However, there were few reports about improvement of quantum efficiency for cationic Ir(III) complexes by increasing the steric hindrance of complexes [41e46], especially through grafting the rigid ring end-capped aliphatic chains, such as carbazole-9-yln-butyl group (here, abbreviated as 'CZB'), on the biscyclometalated ligands and/or ancillary ligands of cationic Ir(III) complexes.…”
Section: Introductionmentioning
confidence: 77%
“…The cyclometalated iridium(III) chloro-bridged dimers were synthesized according to a procedure described in the literature [30,32] …”
Section: Synthesis Of Iridium(iii) Complexes (Ir2~ir4)mentioning
confidence: 99%
“…The absorption band at 264 nm is assigned to the singlet pep * charge transition in the main ligand 2-phenylbenzimidazole. The above absorption bands are similar to the main ligand CzPhBI [10]. The band at 380e490 nm is ascribed to the triplet exciton transition from the metal to ligand charge transition ( 3 MLCT).…”
Section: Photophysical Propertiesmentioning
confidence: 72%
“…Yue et al [10] have reported a series of green iridium(III) complexes with hole-transporting carbazole group as its side chain that could act as single emitting layer. With the introduction of carbazole group, good electroluminescent performances have been achieved with a high luminance over 6000 cd m À2 .…”
Section: Introductionmentioning
confidence: 99%